Clinical care of pregnant and postpartum women with COVID‐19: Living recommendations from the National COVID‐19 Clinical Evidence Taskforce. (29th October 2020) - Vogel, Joshua P.; Tendal, Britta; Giles, Michelle; Whitehead, Clare; Burton, Wendy; Chakraborty, Samantha; Cheyne, Saskia; Downton, Teena; Fraile Navarro, David; Gleeson, Glenda; Gordon, Adrienne; Hunt, Jenny; et al.
Abstract : To date, 18 living recommendations for the clinical care of pregnant and postpartum women with COVID‐19 have been issued by the National COVID‐19 Clinical Evidence Taskforce. This includes recommendations on mode of birth, delayed umbilical cord clamping, skin‐to‐skin contact, breastfeeding, rooming‐in, antenatal corticosteroids, angiotensin‐converting enzyme inhibitors, disease‐modifying treatments (including dexamethasone, remdesivir and hydroxychloroquine), venous thromboembolism prophylaxis and advanced respiratory support interventions (prone positioning and extracorporeal membrane oxygenation). Through continuous evidence surveillance, these living recommendations are updated in near real‐time to ensure clinicians in Australia have reliable, evidence‐based guidelines for clinical decision‐making. Please visit https://covid19evidence.net.au/ for the latest recommendation updates.